A SURVEY ON HOUSEHOLD STORAGE OF MEDICINES IN PUNJAB, PAKISTAN - Hussain, Rizwana; Rashidian, Arash; Hafeez, Asad (Journal of Ayub Medical College Abbottabad, 2019)
Background: Household storage of medicines is a world-wide practice that triggers the irrational use of medicines and consequent threats. The purpose of this research is to explore sources of medicines availability, utilization and reasons of medicines storage in household. Methods: A community-based survey was performed on 900 households in five districts of Punjab, Pakistan from 1st February to 2nd March, 2016. Data was collected through employing a pretested questionnaire, the World Health Organization (WHO) operational package (for assessing, monitoring and evaluating country pharmaceutical situations Level IIb), and analysed by SPSS 23. Results: A mean of 2.94 medicines per household were observed in 900 households visited with 2,648 of total medicines found. Significant number of medicines were analgesics (58.6%) and antibiotics (12.97%). Out of total, 20.4% of household medicines were for current treatments. Left over medicines from past treatments were 8.7%, and 70.9% were anticipated for future use. Household medicines existed in the form of oral tablets, were 89%. Household medicines of 91.2%, were satisfactorily labelled in acute cases and majority were obtained from private pharmacies. Household medicines of 80% were acquired by respondents with post-graduation qualification and 61.2% of the medicines were obtained by respondents with no formal education and in both cases source of medicines was private pharmacies. While overall, 61.5% of respondents took medicines from the private pharmacy. In general, patients got 3.4% of medicines from the primary healthcare facilities. Adherence to medical treatment was very poor. In chronic cases 35.7% of patients left treatment when symptoms improved, while in acute cases 41.1% of the patients showed non-adherence to the treatment. Patients who knew about use of medicines were 92.32%. Conclusions: Maximum medicines stored were for the future use. The main source of medicines found in households was private pharmacies. Antibiotics and analgesic were in common in use. Patient's non-adherence to the treatment was one of the reasons of presence of medicines at home. Keywords: Household medicines storage; Over the counter; Primary healthcare facility; Lady health visitor; Human Development Index